(untitled) (Global Journals of Research in Engineering, 2023)
This simulation study investigates the impact of a 20 variation in physical parameters including porosity tortuosity viscous and thermal characteristic lengths and two newly introduced viscous and thermal shape factor parameters on reflected waves at the first and second interfaces in air-saturated porous media under low-frequency ultrasound excitation The acoustic behavior of air-saturated porous media is modeled using the equivalent fluid theory and the Johnson-Allard model refined by Sadouki Phys Fluids 33 2021 Our results demonstrate that a 20 variation in certain physical parameters significantly affects the reflected waves at the first and second interfaces in the low-frequency domain of ultrasound This study enhances our understanding of the underlying mechanisms governing acoustic wave propagation in air-saturated porous media which is valuable for optimizing ultrasound-based techniques in a range of applications such as nondestructive testing medical imaging and noise pollution control in buildings aircraft automobile industry and civil engineering sectors